1997
DOI: 10.1080/00224549709595466
|View full text |Cite
|
Sign up to set email alerts
|

Helping Behaviors and the Perception of Helping Intentions Among Chinese Students

Abstract: A questionnaire survey explored the kinds of helping behaviors given and received by Chinese college students and the kinds of explanations offered for these behaviors. Helping behaviors reported by the Chinese students paralleled those of U.S. college students in McGuire (1994); the behaviors were sorted, according to her typology, into casual, substantial personal, emotional, and emergency helping. Four categories of perceived intentions behind helping behaviors were identified: altruistic, normative, relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Perrea et al (2014) highlighted that Chinese consumers were guided by altruistic predispositions because of their collectivistic values. In addition, Li (1997) suggested that altruism was one of the key categories of perceived intentions lying behind the helping behaviors of Chinese. Our results also extend Liu and Cohen's (2010) finding that Chinese are keen to altruistically help others in their organizations without expecting direct or indirect rewards.…”
Section: Discussionmentioning
confidence: 99%
“…Perrea et al (2014) highlighted that Chinese consumers were guided by altruistic predispositions because of their collectivistic values. In addition, Li (1997) suggested that altruism was one of the key categories of perceived intentions lying behind the helping behaviors of Chinese. Our results also extend Liu and Cohen's (2010) finding that Chinese are keen to altruistically help others in their organizations without expecting direct or indirect rewards.…”
Section: Discussionmentioning
confidence: 99%
“…Even though helping behavior resulting from both motives may lead to the same helping actions received by the recipient, the recipient can respond to these two categories of helping motives differently. In particular, when the recipient attributes the helper’s helping motives to other-oriented values, the recipient perceives that the helper has a genuine desire to help and benevolently intends to improve others’ well-being (Bolino, 1999; Li, 1997). More importantly, helping motives signifying selfless and genuine care for others lead to positive and favorable evaluations of the helper and helping actions (Lemoine et al , 2015).…”
Section: Model Developmentmentioning
confidence: 99%
“…As such, helping behavior with self-oriented motives can be inferred by the recipient as an exploitation resulting from the helper's opportunistic and calculative intents. Although helping actions motivated by self-oriented motives benefit the recipient's task performance, helping with self-oriented motives is generally viewed as egoistic and self-serving (Li, 1997;Rioux and Penner, 2001). Such view of self-oriented helping can contribute to the recipient's feeling of being used as a stepping stone by the helper to obtain personal gains.…”
mentioning
confidence: 99%